Analysis of Disposal Slope Safety Factor in Determining the Safe Distance of Dumping Sequence at Disposal X in Sorowako Area, East Luwu Regency, South Sulawesi Province - Nur Alifia Suparman; Busthan Azikin (CV Insight Publisher, 2025)
Slope stability assessment is essential in open discharge designs to prevent failure during discharge operations. This study investigated the safety factors of the disposal slope to determine the safe disposal sequence distance at Disposal X, Sorowako, South Sulawesi, Indonesia. Stability evaluation was carried out using the Limit Equilibrium Method with the Morgenstern–Price formulation at GeoStudio SLOPE/W 2022. The analysis incorporates slope geometry, laboratory-tested geotechnical parameters, equipment-induced soil pressure, and topographic data. Three representative cross-sections were analyzed to identify critical conditions. Preliminary results show that the calculated safety factor is below the minimum regulatory requirement of 1.3. Therefore, design adjustments are applied by modifying the elevation of the slope sequence and controlling the discharge distance. After the redesign, the safety factor increased to 1,360, 1,362, and 1,374, indicating stable conditions. The optimized configuration meets regulatory standards and provides a reliable technical reference for safe disposal operations in the disposal area.